Fabrication of a cell irradiation technique by alpha-particles using allyl diglycol carbonate (ADC) detector and micro-capillary tubes - Runas Yakup Sula; Asaad Hamid Ismail (Journal of the Pakistan Medical Association)
Objective: To study the impact of micro-alpha irradiation collimator with a specific design to irradiate specific normal or up-normal cells using capillary tubes and nuclear track detector type CR-39.